THE EFFECT OF PHYSICAL WORK ENVIRONMENT, WORK SAFETY, OCCUPATIONAL HEALTH AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY - RAHMI, TIKA ERRY; WIBOWO, SIGIT (INDONESIAN RESEARCH SOCIETY, 2018)
Health and Work Discipline on Employee Productivity (Study on Employees of PT. PLN (Persero) Central Java & D.I.Y) Distribution Regulatory Areas